2016
DOI: 10.1071/ah15115
|View full text |Cite
|
Sign up to set email alerts
|

The role of technology in Australian youth mental health reform

Abstract: Abstract. This paper describes the extent and nature of Internet use by young people, with specific reference to psychological distress and help-seeking behaviour. It draws on data from an Australian cross-sectional study of 1400 young people aged 16 to 25 years. Nearly all of these young people used the Internet, both as a source of trusted information and as a means of connecting with their peers and discussing problems. A new model of e-mental health care is introduced that is directly informed by these fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 15 publications
3
45
0
Order By: Relevance
“…From a service level perspective, the priorities can serve to identify effective service features and recommend a best practice model of care for young people. The integration of digital technologies within such a model (ie, offering faceto-face, mobile and online services) has the potential to enhance helpseeking behaviours, access to therapy, service engagement and costeffectiveness (Alvarez-Jimenez et al, 2012;Burns et al, 2016;Lal & Adair, 2014;Rickwood, Webb, Kennedy, & Telford, 2016). For LMICs in particular, approaches that incorporate digital technologies, lay health workers and the integration of mental health care into larger frontline primary health and community development initiatives could reduce the treatment gap (Arjadi et al, 2018;Patel et al, 2008).…”
Section: Box 3 Overarching Considerations For Youth Mental Health Resmentioning
confidence: 99%
“…From a service level perspective, the priorities can serve to identify effective service features and recommend a best practice model of care for young people. The integration of digital technologies within such a model (ie, offering faceto-face, mobile and online services) has the potential to enhance helpseeking behaviours, access to therapy, service engagement and costeffectiveness (Alvarez-Jimenez et al, 2012;Burns et al, 2016;Lal & Adair, 2014;Rickwood, Webb, Kennedy, & Telford, 2016). For LMICs in particular, approaches that incorporate digital technologies, lay health workers and the integration of mental health care into larger frontline primary health and community development initiatives could reduce the treatment gap (Arjadi et al, 2018;Patel et al, 2008).…”
Section: Box 3 Overarching Considerations For Youth Mental Health Resmentioning
confidence: 99%
“…Young people are increasingly relying on the Internet to find answers about their health concerns. For example, in Australia, a national survey in 2012-13 revealed that 53% of young people aged between 16 and 25 years with moderate and very high levels of psychological distress sought Web-based information related to a mental health and/or alcohol or other substance use problem; the majority found this information to be helpful [ 23 ]. In other surveys, young people reported feeling comfortable accessing Web-based mental health tools because they felt they were anonymous, welcoming, less stigmatizing, and, for the most part, trustworthy [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, these three stakeholder groups have focused on different aspects of implementation. Researchers have studied user satisfaction [13, 15, 16] to determine that eMental healthcare technologies are acceptable to children and adolescents, and their parents and mental healthcare professionals. Healthcare planners and policymakers have discussed issues such as the cost and feasibility of eMental healthcare technologies to deliver pediatric mental healthcare [17].…”
Section: Introductionmentioning
confidence: 99%